Oral Cancer: Awareness Among People of Biratnagar - Chaulagain, Durga Devi; Parajuli, Kamal Prasad; Khatiwada, Bhumika (Journal of Nobel Medical College, 2018)
Background: Increased use of tobacco and tobacco products result into increment of patients with oral cancer. Many people are still unaware of the consequences of chewing tobacco. Approximately 19% of participants had adequate knowledge of awareness, large number of participants, i.e., 73% had moderate knowledge of awareness and 8% of the participants had inadequate level of awareness about oral cancer. Methods and materials: Analytical cross-sectional research design was used for the study. Samples were selected by non-probability purposive sampling technique. Structured questionnaire was used to collect data from respondents. Frequencies, mean and standard deviations were used to describe the socio-demographic variables. Independent t-test and one-way ANOVA test were used to find the main difference of awareness scores by socio-demographic variables. Results: Among 90 participants, 18% had adequate level of awareness, 73% had moderate and 7.8% of participants had inadequate level of awareness regarding oral cancer. Conclusion: The study showed that awareness regarding oral cancer among the people of Biratnagar Metropolitan City is moderate. The study emphasizes that the effects must be made to make people aware of oral cancer.Journal of Nobel Medical CollegeVolume 7, Number 1, Issue 12, January-June 2018, Page: 60-64